COVID-19 in-vitro Diagnostics: State-of-the-Art and Challenges for Rapid, Scalable, and High-Accuracy Screening - Habli, Zeina; Saleh, Sahera; Zaraket, Hassan; Khraiche, Massoud L. (Frontiers in Bioengineering and Biotechnology, 2021)
The world continues to grapple with the devastating effects of the current COVID-19 pandemic. The highly contagious nature of this respiratory disease challenges advanced viral diagnostic technologies for rapid, scalable, affordable, and high accuracy testing. Molecular assays have been the gold standard for direct detection of the presence of the viral RNA in suspected individuals, while immunoassays have been used in the surveillance of individuals by detecting antibodies against SARS-CoV-2. Unlike molecular testing, immunoassays are indirect testing of the viral infection. More than 140 diagnostic assays have been developed as of this date and have received the Food and Drug Administration (FDA) emergency use authorization (EUA). Given the differences in assasy format and/or design as well as the lack of rigorous verification studies, the performance and accuracy of these testing modalities remain unclear. In this review, we aim to carefully examine commercialized and FDA approved molecular-based and serology-based diagnostic assays, analyze their performance characteristics and shed the light on their utility and limitations in dealing with the COVID-19 global public health crisis.